Antropocentryczna filozofia Jana Pawła II - Szocik, Konrad (Slavia Occidentalis, 2013)
This paper analyzes the metaphysical basis of John Paul II’s philosophy that made possible the propagation of the ideas of unity and ecumenism, and the underlying importance of individuality. Developed by The Second Vatican Council “the contemporizing” of the Church’s position, required a rejection of thomistic, real metaphysics, the ontological concept of truth, the truth of a single religion or a real model of human cognition. This paper underlines the acceptance of the secularized world’s ideas and their influence on changes in Church teaching during John Paul II’s pontificate.